Early childhood vaccination coverage and timeliness by macro-area of origin in children born to foreign women residing in Italy. (July 2021) - Spadea, T.; Fano, V.; Piovesan, C.; Rusciani, R.; Salamina, G.; Greco, G.; Colaiocco, G.; Ramigni, M.; Declich, S.; Petrelli, A.; Pezzotti, P.; Fabiani, M.
Abstract: Objectives: Country of origin might affect vaccine uptake in children born to immigrants. We aimed to evaluate differences in childhood vaccination coverage (VC) and timeliness by macro-area of origin of foreign mothers residing in Italy. Study design: Multicentre retrospective birth cohorts. Methods: We analysed data of 23, 287 children born in 2009–2014 to foreign women in the cities of Rome, Turin and Treviso. We retrieved data through record-linkage of the population, vaccination and birth registries. We estimated VCs at different ages for vaccines against tetanus, measles and meningococcal group-C, using the Kaplan–Meier method. Factors associated with vaccine uptake were evaluated using multilevel Poisson models. Results: Estimates of VC at any age and for all antigens were significantly lower in children born to women from Asia and higher in children born to women from Africa, as compared to other macro-areas. Similar differences by area of origin were observed for timeliness; independently of mother's sociodemographic characteristics and neonatal outcomes, the probability of delay vaccination after 2 years of age for each antigen was highest in children born to women from Asia. The risk of missed vaccination for all antigens was significantly higher in children born to younger and unemployed women. Conclusions: Factors related to area of origin (e.g., cultural habits, language skills) are likely to affect parents' decision to vaccinate their children. These factors, as well as sociodemographic characteristics, should be adequately investigated and addressed to increase vaccine uptake in foreign children, especially those born to Asian women.